2014
DOI: 10.4236/ojped.2014.41009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcome of Preterm Admissions at the Neonatal Unit of a Tertiary Health Centre in Southern Nigeria

Abstract: Background: Preterm babies have increased risk of morbidity and mortality which is inversely related to both gestational age and birth weight. Most preterm births result from maternal or foetal medical conditions. Objectives: To determine the prevalence and outcome of preterm admissions at the Special Care Baby Unit of the Niger Delta University Teaching Hospital, as well as their morbidity pattern and risk factors for preterm birth. Methodology: All preterm babies admitted from January 2010 to December 2012 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
37
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 30 publications
13
37
9
Order By: Relevance
“…The slightly lower level found by Mokuola et al 25 may be due to the shorter duration of the study and their stricter inclusion criteria, precluding multiple gestations and major malformations. In contrast to our findings, Kunle-Olowu et al 26 in Niger-Delta area of Nigeria and Onwuanaku et al 27 in North Central Nigeria reported that 24% and 31.3% of infants admitted in their facilities were preterm, respectively. Although the exact cause of this very high preterm delivery rate is unclear in the oil-polluted Niger-Delta, the latter study in northern Nigeria comprised only a laboratory-tested cohort, inadvertently introducing a selection bias 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…The slightly lower level found by Mokuola et al 25 may be due to the shorter duration of the study and their stricter inclusion criteria, precluding multiple gestations and major malformations. In contrast to our findings, Kunle-Olowu et al 26 in Niger-Delta area of Nigeria and Onwuanaku et al 27 in North Central Nigeria reported that 24% and 31.3% of infants admitted in their facilities were preterm, respectively. Although the exact cause of this very high preterm delivery rate is unclear in the oil-polluted Niger-Delta, the latter study in northern Nigeria comprised only a laboratory-tested cohort, inadvertently introducing a selection bias 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…Most common clinical conditions of neonates in our study are sepsis, RDS, prematurity and seizures making 71.2% of all diseases. These results are similar to many local studies, 2,3,13,14 as well as researches in other countries 5,[15][16][17][18] with almost the same disease pattern. In contrast, a research carried out in Peshawar had maximum admissions due to low birth weight and IUGR.…”
Section: Discussionsupporting
confidence: 91%
“…The commonest risk factor for Prematurity was PROM followed by multiple pregnancy and lack of ANC. This is similar to findings by Kunle-Olowu et al [11]. Other studies in Nigeria [16] [17] [18] have reported multiple pregnancy as a risk factor for preterm delivery.…”
Section: Discussionsupporting
confidence: 82%
“…The number of male babies were more than the females and comparable to that reported by Kunle-Olowu et al [11]. McGil Ugwu [10] and Zeleke et al [13] in Ethiopia reported more preterm females.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation